The Relationship of Emotional Intelligence of Fifth Grade Students to Bullying Behavior in Elementary Schools - .Zelika, Zelika; Maksum, Arifin; Nurhasanah, Nina; Zelika, Zelika (JURNAL PENDIDIKAN DASAR NUSANTARA, 2024)
Education in Indonesia is experiencing a bullying emergency. Bullying is aggressive behavior that involves an imbalance of power followed by oppression and solely to make others feel uncomfortable or afraid. Bullying cases in educational institutions, especially in elementary schools, are increasing every year. This is caused by various factors, including external and internal factors. External factors include parenting patterns, the environment, and culture from outside. While internal factors come from within the students, including feelings of empathy and student personality related to emotional intelligence. Therefore, this study aims to determine the relationship between emotional intelligence and bullying behavior in elementary schools. The population in this study was grade V at SDN 12 Pagi Cengkareng Timur with a sample of 30 students. Sampling in this study was determined using a purposive sampling technique because it met certain criteria, such as sample homogeneity which was in the age range of 11-12 years, a sample size sufficient to achieve the desired depth of analysis, and ease of access to members of the population. This study is a quantitative study with a data collection technique using a questionnaire instrument that goes through a statistical test stage, such as validity and reliability tests. This study uses two analysis techniques, namely univariate analysis and bivariate analysis. The results of the correlation test show that the Sig. value is 0.019 <0.05 with r count 0.426> r table 0.361, so there is a positive and significant relationship between emotional intelligence and bullying behavior. The higher the level of emotional intelligence of a student, the lower the tendency of bullying behavior.